Justice in the Tea Estate Community in Sri Lanka: An Explanation through Freedom-based Capability Approach - Dishanka, Sajitha; Ikemoto, Yukio (Journal of Social and Development Sciences, 2018)
Sustainability in economic development is fundamentally linked to human well-being which should be fairly reflected in freedom. This normative concern has been the thematic phenomenon in scholarly discussions advocated by many egalitarians. The well-being of tea estate community in Sri Lanka has been in various stakeholder discussions as their socio-economic freedom is exogenously determined and controlled. Ironically, this situation has evidenced a substantial adverse impact on their present work performance and future workforce participation symbolizing the labor problem within the tea estate community. Grounded on the theoretical foundation of Amartya Sen’s capability approach and, authors’ mixed method field surveys, this paper discusses the importance of enhancing justice within this community by improving their freedom to access better complex capabilities such as social status and independence. Although, the outcomes of the positivistic study provided with adequate evidence for the above claim, our qualitative inquiry confirmed and witnessed the aforementioned subjective reality.